دور الدبلوماسية العامة في السياسة المعاصرة - العلو نضال (Latakia University Journal - Economic and Legal Sciences Series, 2018)
In recent years, against the backdrop of the processes of globalization and the rapid development of information and communication technologies, the capacity of citizens to influence the policies of their states has significantly increased. In this regard, governments of countries seeking to maintain and expand their influence in the world, try to take these new trends into account when planning and implementing their foreign policy. It can be noted that the importance of these political processes is indicate the need in the interests of increasing the effectiveness of state foreign policy; it is more effective to use the resource of the public diplomacy. The public diplomacy is an integral part foreign policy of the state. What is the impact of public diplomacy technologies on political processes? في السنوات الأخيرة ، وعلى خلفية عمليات العولمة والتطور السريع لتكنولوجيا المعلومات والاتصالات ، زادت قدرة المواطنين على التأثير في سياسات دولهم بشكل كبير. وفي هذا الصدد ، تحاول حكومات البلدان التي تسعى للحفاظ على نفوذها وتوسعه في العالم ، أخذ هذه الاتجاهات الجديدة بعين الاعتبار عند تخطيط وتنفيذ سياستها الخارجية. تجدر الإشارة إلى أن أهمية هذه العمليات السياسية تشير إلى الحاجة إلى زيادة فعالية السياسة الخارجية للدولة، فإنه أكثر فعالية لاستخدام موارد الدبلوماسية العامة. الدبلوماسية العامة جزء لا يتجزأ من السياسة الخارجية للدولة. ما هو تأثير تكنولوجيات الدبلوماسية العامة على العمليات السياسية؟